Geological Structures of the Kinta Valley Revisited Using Drainage Anomalies - Choong Chee Meng, Manuel Pubellier, . (2015)
ore than 50% of the surface of Kinta Valley is covered by alluvium overlying Paleozoic sequences and Late Triassic granitic intrusions. The alluvium of the valley is thin (mostly less than 30 m thick). Limestone and shale are the dominant lithologies cropping out in the valley, and they have been severely deformed. Unfortunately, these rocks are restricted to small areas of the valley and they are highly weathered, thus making the correlations between outcrops and structural interpretation commonly speculative.